Pengaruh Kecerdasan Emosional Dan Persepsi Siswa Tentang Variasi Gaya Mengajar Guru Terhadap Prestasi Belajar Pendidikan Kewirausahaan Pada Siswa Kelas X SMK Muhammadiyah Kartasura Tahun Ajaran 2015/2016 - Efendi, Arifin, Drs.Nur Chusni, SE., M.Ag (2016)
This study aims to determine; 1) Effect of emotional intelligence on student achievement; 2) Effect of students' perception about the variety of teaching styles of teachers on student achievement; 3) Effect of effect of emotional intelligence and perceptions of students about the variety of teaching styles of teachers on student achievement. This research is descriptive quantitative research with a conclusion through statistical methods. The population in this study were all students of class X SMK Muhammadiyah Kartasura academic year 2015/2016. samples are taken as 114 students with simple random sampling. Necessary data obtained through questionnaires and documentation. The questionnaire previously tested and tested for validity and reliability were tested. Data analysis technique used is multiple linear regression analysis, t-test, F, and the relative contribution and effective. The results of the regression analysis obtained regression equation: Y = 37.176 + 0.548 X1 + 0.388 X2. The equation shows that learning achievement is influenced by emotional intelligence and perceptions of students about the variety of teaching styles of teachers. The conclusions drawn are: 1) Emotional Intelligence on student achievement acceptable. This is based on multiple linear regression analysis (t test) note that tcount> ttable, 3.868> 2.000 and the significance value <0.05, namely 0.000 with the relative contribution of 59% and the effective contribution of 19.6%. 2) Students' perceptions about the variety of teaching styles of teachers on student achievement acceptable. This is based on multiple linear regression analysis (t test) note that tcount> ttable, namely 2.911> 2.000 and the significance value <0.05, namely 0.004 with the relative contribution of 41% and the effective contribution of 13.6%. 3) Emotional intelligence and students' perception about the variety of teaching styles of teachers on student achievement acceptable. This is based on multiple linear regression analysis of variance (F test) is known that F count> F table, ie 27.555> 3.150 and the significance value <0.05, namely 0.000. 4) The coefficient of determination (R2) of 0.332 indicates that the influence of emotional intelligence and perceptions of students about the variety of teaching styles of teachers on student achievement is 33.2%, while the rest influenced by other variables.